2021
DOI: 10.1002/pros.24185
|View full text |Cite
|
Sign up to set email alerts
|

SRSF‐1 and microvessel density immunohistochemical analysis by semi‐automated tissue microarray in prostate cancer patients with diabetes (DIAMOND study)

Abstract: Objective: To study the association between insulin receptors (isoforms α and β), insulin growth factor-1 (IGF1) and serine/arginine splicing factor 1 (SRSF-1) in patients with prostate cancer (PC) and diabetes. Materials and Methods:We retrospectively analyzed data from 368 patients who underwent surgery for PC or benign prostatic hyperplasia (BPH) between 2010 and 2020 at the Department of Urology, University of Catania. Tissue microarray slides were constructed and they were stained for androgen receptor (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
0
34
0
1
Order By: Relevance
“…SRSF1 is an RNA-binding protein with proto-oncogenic function, being involved in angiogenesis, cell migration and tumor proliferation of several types of human neoplasms, including gliomas, malignant mesotheliomas, and breast, colorectal and prostate cancers [18,[20][21][22][23][24][25]. SRSF1 immunoexpression was positively associated with worse outcome, androgen-receptor status and Ki-67 proliferation rate in prostatic adenocarcinoma [27]; a significant correlation between SRSF1, MVD and shorter overall survival times was also found in fluoro-edenite-induced malignant mesothelioma [26]. In the present paper we provided the first immunohistochemical evidence of the poor prognostic role of this protein in UM; in more detail, we found a statistically significant correlation between higher SRSF1 immunohistochemical expression, higher MVD levels and poorer prognosis in terms of metastatic spread and lower metastasis-free-survival in UM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SRSF1 is an RNA-binding protein with proto-oncogenic function, being involved in angiogenesis, cell migration and tumor proliferation of several types of human neoplasms, including gliomas, malignant mesotheliomas, and breast, colorectal and prostate cancers [18,[20][21][22][23][24][25]. SRSF1 immunoexpression was positively associated with worse outcome, androgen-receptor status and Ki-67 proliferation rate in prostatic adenocarcinoma [27]; a significant correlation between SRSF1, MVD and shorter overall survival times was also found in fluoro-edenite-induced malignant mesothelioma [26]. In the present paper we provided the first immunohistochemical evidence of the poor prognostic role of this protein in UM; in more detail, we found a statistically significant correlation between higher SRSF1 immunohistochemical expression, higher MVD levels and poorer prognosis in terms of metastatic spread and lower metastasis-free-survival in UM.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between SRSF1 and MVD, previous studies demonstrated that SRSF1 had a stimulatory function on tumor angiogenesis, resulting in a switch in the pro-angiogenic/anti-angiogenic ratio of VEGFA [17][18][19][20][21]; in this regard, Barbagallo et al first reported the complex relationship between circSMARCA5, a specific subtype of circRNAs with a tumor-suppressor role, and SRSF1, demonstrating that the downregulation of circSMARCA5 along with the concomitant upregulation of SRSF1 led to increased cell migration and angiogenesis in human glioblastoma tissue and cell lines [17][18][19]. The MVD count, despite not representing the best method to evaluate tumor angiogenesis, is a semi-quantitative "surrogate" of this process [27]; accordingly, the positive correlation found in our cohort between SRSF1 and MVD led us to hypothesize that SRSF1 has a pro-angiogenic role also in UM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations